ACGME Core Competency Training, Mentorship, and Research in Surgical Subspecialty Fellowship Programs - Francesca Monn, M.; Wang, Ming-Hsien; Gilson, Marta M.; Chen, Belinda; Kern, David; Gearhart, Susan L. (Journal of surgical education, 2013)
To determine the perceived effectiveness of surgical subspecialty training programs in teaching and assessing the 6 ACGME core competencies including research. Cross-sectional survey. ACGME approved training programs in pediatric urology and colorectal surgery. Program Directors and recent trainees (2007-2009). A total of 39 program directors (60%) and 57 trainees (64%) responded. Both program directors and recent trainees reported a higher degree of training and mentorship (75%) in patient care and medical knowledge than the other core competencies (p<0.0001). Practice based learning and improvement, interpersonal and communication, and professionalism training were perceived effective to a lesser degree. Specifically, in the areas of teaching residents and medical students and team building, program directors, compared with recent trainees, perceived training to be more effective, (p = 0.004, p = 0.04). Responses to questions assessing training in systems based practice ubiquitously identified a lack of training, particularly in financial matters of running a practice. Although effective training in research was perceived as lacking by recent trainees, 81% reported mentorship in this area. According to program directors and recent trainees, the most effective method of teaching was faculty supervision and feedback. Only 50% or less of the recent trainees reported mentorship in career planning, work-life balance, and job satisfaction. Not all 6 core competencies and research are effectively being taught in surgery subspecialty training programs and mentorship in areas outside of patient care and research is lacking. Emphasis should be placed on faculty supervision and feedback when designing methods to better incorporate all 6 core competencies, research, and mentorship.